The role of SIMA as Corporate Social Responsibility (CSR) in enhancing Standard Chartered product and brand image awareness in Malaysia / Mohd Atasha Alias - Alias, Mohd Atasha (Faculty of Business and Management, 2010)
This research examined the effects of Scope International Malaysia Academy (SIMA) as SCR in enhancing Standard Chartered product and brand image awareness in Malaysia. The purpose of this research is to identify the effects of SIMA as CSR activity in producing knowledgeable workers, high skill workers and financial professionals. This is to find out whether the initial purposes of implementing CSR activity will really produce to the effects wanted. To carry out this research, a total of 34 sets of survey questionnaires were distributed to the SIMA alumni who are currently working with Scope International. A total of 34 participants were identified that could participate in the survey. The reliability analysis, frequency distribution analysis, and Pearson’s correlation analysis are used in the research to analyze and interpret the results. The research findings show that the increasing trend in Standard Chartered product and brand image awareness in Malaysia is the most important factor that encourages CSR activity by Scope International. Furthermore, the research also confirmed that implementing CSR in Scope International can improve skills and knowledge of workers, producing financial professional and increase the awareness of Standard Chartered product and brands among Malaysian. In addition, the research results also established that there is correlation between the factors and the effects of initiating CSR practices. This research can be beneficial to the commercial banking sector in Malaysia and serve as a reference for them to further exploit the benefits and advantages of implementing CSR. This research examined the effects of Scope International Malaysia Academy (SIMA) as SCR in enhancing Standard Chartered product and brand image awareness in Malaysia. The purpose of this research is to identify the effects of SIMA as CSR activity in producing knowledgeable workers, high skill workers and financial professionals. This is to find out whether the initial purposes of implementing CSR activity will really produce to the effects wanted. To carry out this research, a total of 34 sets of survey questionnaires were distributed to the SIMA alumni who are currently working with Scope International. A total of 34 participants were identified that could participate in the survey. The reliability analysis, frequency distribution analysis, and Pearson’s correlation analysis are used in the research to analyze and interpret the results. The research findings show that the increasing trend in Standard Chartered product and brand image awareness in Malaysia is the most important factor that encourages CSR activity by Scope International. Furthermore, the research also confirmed that implementing CSR in Scope International can improve skills and knowledge of workers, producing financial professional and increase the awareness of Standard Chartered product and brands among Malaysian. In addition, the research results also established that there is correlation between the factors and the effects of initiating CSR practices. This research can be beneficial to the commercial banking sector in Malaysia and serve as a reference for them to further exploit the benefits and advantages of implementing CSR.